2018
DOI: 10.3390/math6090171
|View full text |Cite
|
Sign up to set email alerts
|

Almost Periodic Solutions of First-Order Ordinary Differential Equations

Abstract: Approaches to estimate the number of almost periodic solutions of ordinary differential equations are considered. Conditions that allow determination for both upper and lower bounds for these solutions are found. The existence and stability of almost periodic problems are studied. The novelty of this paper lies in the fact that the use of apparatus derivatives allows for the reduction of restrictions on the degree of smoothness of the right parts. In the works of Lebedeva [1], regarding the number of periodic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
0
12
0
1
Order By: Relevance
“…Most of the real systems will exhibit the non-linear and unstable behavior and based on the operating region, it can work as complete or semi-stable system. When the operating region is varied, its stability also will be affected and hence, it is necessary to implement an optimally designed PID to provide essential stability to the system even though the conditions of the system are changing due to uncertainties [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the real systems will exhibit the non-linear and unstable behavior and based on the operating region, it can work as complete or semi-stable system. When the operating region is varied, its stability also will be affected and hence, it is necessary to implement an optimally designed PID to provide essential stability to the system even though the conditions of the system are changing due to uncertainties [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Neto in [2] states that for equation (1), we are unable to have upper bound for number of periodic solutions until some coefficients are restricted. Kadry in [3] gives conditions that allow determination for both upper and lower bounds. Our basic focus is to acquire highest periodic solutions of any class of the type (1); our main concern in this paper is this nearby question of bifurcation.…”
Section: Introductionmentioning
confidence: 99%
“…Periodic solutions take an important part in the qualitative theory of differential equations and in applied problems [3]. The analysis problems for periodic solutions of differential equations arise in classical mechanics, celestial mechanics [4][5][6][7][8][9][10][11][12][13][14][15], space robotics [16][17][18][19][20][21][22][23][24], in modeling of economic processes [25][26][27][28][29]. However, there is no general approach to study periodic solutions of differential equations.…”
Section: Introductionmentioning
confidence: 99%
“…A more general result in this direction was obtained by V.M. Lebedeva, having shown that an equation in which the right-hand side is a 4th order polynomial, can have any preassigned number of periodic solutions [5,33]. Our idea in this paper is to reject the requirement of polynomiality of the right-hand side of the equation under study and proposed a different approach for obtaining the upper and lower estimates for the number of periodic solutions.…”
mentioning
confidence: 99%